2021
DOI: 10.3389/fonc.2021.650360
|View full text |Cite
|
Sign up to set email alerts
|

DDX54 Plays a Cancerous Role Through Activating P65 and AKT Signaling Pathway in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the most malignant cancers, and its incidence is still steadily increasing. The DDX RNA helicase family members have been found to play a role in various cancers; however, the role of DDX54 in colorectal cancer is still unclear and needed to be defined. Here, we found DDX54 was overexpressed in CRC tissues by the label-free mass spectrum, which was also verified in tissue microarray of colon cancer, as well as the CRC cell lines and TCGA database. High DDX54 level was correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…As for the regulatory mechanisms underlying the impact of DDX55 on β‐catenin signaling, we concentrated on the correlation between DDX55 and PIK3CA, an oncogene encoding PI3Kα catalytic subunit and acting as a well‐known activator of AKT in tumorigenesis, under the guidance of the sequencing analysis 51 . Consistent with the existing evidence with regard to the associations between DEAD‐box proteins and the PI3K/Akt pathway, our data demonstrated that DDX55 could significantly enhance PIK3CA expression both at the mRNA and protein levels, and further reinforced β‐catenin protein stability dependent on PI3K/Akt/GSK‐3β pathway activation 46,52–54 . A high percentage of aberrant activation of the Wnt/β‐catenin signaling (30%–40%) and the PI3K/Akt signaling (nearly 50%) have been reported in human HCC samples, which highlights the potential of DDX55 as a valuable therapeutic target in those HCC 34,55 …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As for the regulatory mechanisms underlying the impact of DDX55 on β‐catenin signaling, we concentrated on the correlation between DDX55 and PIK3CA, an oncogene encoding PI3Kα catalytic subunit and acting as a well‐known activator of AKT in tumorigenesis, under the guidance of the sequencing analysis 51 . Consistent with the existing evidence with regard to the associations between DEAD‐box proteins and the PI3K/Akt pathway, our data demonstrated that DDX55 could significantly enhance PIK3CA expression both at the mRNA and protein levels, and further reinforced β‐catenin protein stability dependent on PI3K/Akt/GSK‐3β pathway activation 46,52–54 . A high percentage of aberrant activation of the Wnt/β‐catenin signaling (30%–40%) and the PI3K/Akt signaling (nearly 50%) have been reported in human HCC samples, which highlights the potential of DDX55 as a valuable therapeutic target in those HCC 34,55 …”
Section: Discussionsupporting
confidence: 72%
“…51 Consistent with the existing evidence with regard to the associations between DEAD-box proteins and the PI3K/ Akt pathway, our data demonstrated that DDX55 could significantly enhance PIK3CA expression both at the mRNA and protein levels, and further reinforced β-catenin protein stability dependent on PI3K/Akt/GSK-3β pathway activation. 46,[52][53][54] A high percentage of aberrant activation of the Wnt/β-catenin signaling (30%-40%) and the PI3K/Akt signaling (nearly 50%) have been reported in human HCC samples, which highlights the potential of DDX55 as a valuable therapeutic target in those HCC. 34,55 Emerging evidence has suggested that DEAD-box proteins generally function as components of multi-protein complexes and act as a transcriptional co-activator in gene expression regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Cao Several DDX family members are known to regulate mRNA translation in cancer cells, and inhibitors targeting DDX proteins are currently under development. DDX54 was reported to play a cancerous role in colorectal cancer [29]. Our data suggest that high DDX54 expression predicts poor PFS and OS in LUAD patients.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, circ-CELF1 knockdown weakened the binding relation between DDX54 and NFAT5. DDX54 belongs to the RNA helicase family, which affects important cellular process [31]. DDX54 has also been reported to enhance the mRNA stability of SIK2 in triple-negative breast cancer [32].…”
Section: Discussionmentioning
confidence: 99%